2010
DOI: 10.1186/1745-7580-6-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of conformational B-cell Epitopes in an antigen from its primary sequence

Abstract: BackgroundOne of the major challenges in the field of vaccine design is to predict conformational B-cell epitopes in an antigen. In the past, several methods have been developed for predicting conformational B-cell epitopes in an antigen from its tertiary structure. This is the first attempt in this area to predict conformational B-cell epitope in an antigen from its amino acid sequence.ResultsAll Support vector machine (SVM) models were trained and tested on 187 non-redundant protein chains consisting of 2261… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
235
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(240 citation statements)
references
References 46 publications
4
235
0
1
Order By: Relevance
“…The variable region B amino acid sequences of the mycobacterial G37-C inoculum and the week 8 variant were analyzed for the presence of B-cell epitopes with the EMBOSS antigenic (http://emboss.bioinformatics.nl/cgi-bin/emboss/antigenic) and BepiPred 1.0 (http://www.cbs.dtu.dk/services/BepiPred/) ( [51]) programs using a wide range of epitope lengths and thresholds, respectively. The full-length MgpB protein of strain G37-C was analyzed for predicted conformational B-cell epitopes using the CBTOPE program (http://www .imtech.res.in/raghava/cbtope/ [52]) with a support vector machine threshold of Ϫ0.3. The sequence of the full-length week 8 variant MgpB is unknown and consequently was not searched for conformational epitopes.…”
Section: Methodsmentioning
confidence: 99%
“…The variable region B amino acid sequences of the mycobacterial G37-C inoculum and the week 8 variant were analyzed for the presence of B-cell epitopes with the EMBOSS antigenic (http://emboss.bioinformatics.nl/cgi-bin/emboss/antigenic) and BepiPred 1.0 (http://www.cbs.dtu.dk/services/BepiPred/) ( [51]) programs using a wide range of epitope lengths and thresholds, respectively. The full-length MgpB protein of strain G37-C was analyzed for predicted conformational B-cell epitopes using the CBTOPE program (http://www .imtech.res.in/raghava/cbtope/ [52]) with a support vector machine threshold of Ϫ0.3. The sequence of the full-length week 8 variant MgpB is unknown and consequently was not searched for conformational epitopes.…”
Section: Methodsmentioning
confidence: 99%
“…A number of researchers have reported identifying CR of Abs and Ags by analysis of publicly available crystal structures (10)(11)(12). A large body of work in this field is aimed at identifying CR as a means of developing algorithms for predicting B cell epitopes (10,(13)(14)(15)(16)(17), whereas others have focused on analyzing or predicting CR in CDR of Abs (8,(18)(19)(20). The majority of the existing studies define two residues to be in contact when they are within a specified distance of each other.…”
mentioning
confidence: 99%
“…The majority of the existing studies define two residues to be in contact when they are within a specified distance of each other. Many researchers use 4 Å as the definition of CR (10,(14)(15)(16)(17), and the Molecular Modeling Database (21), at the National Center for Biotechnology Information, defines protein interactions using a 4-Å cutoff. One group has published several works using 6 Å (13,20,22) and reported that their conclusions were unaffected by cutoffs ranging from 4 to 6 Å (20).…”
mentioning
confidence: 99%
“…However, many B-cell epitopes are conformational and discontinuous (Braga-Neto and Marques, 2006; Ansari and Raghava, 2010), corresponding to the tridimensional features on the surface of the antigen where recognition by the immune system occurs (BragaNeto and Marques, 2006). This creates difficulties for the bioinformatic prediction of B-cell epitopes.…”
Section: Computational Predictive Methodsmentioning
confidence: 99%